The Neurobiological Basis of the Distress Thermometer: A PET Study in Cancer Patients. (6th November 2013) - Castelli, L.; Tonello, D.; D'Agata, F.; Caroppo, P.; Baudino, B.; Zotta, M.; Cauda, S.; Pinessi, L.; Mortara, P.; Grassi, L.; Bisi, G.; Torta, R.
Abstract The objective of this study was to investigate the possible associations between the Distress Thermometer (DT) scores and the brain metabolism of structures involved in stress response. Twenty‐one cancer patients were assessed using the DT, Problem Checklist and Hospital Anxiety and Depression Scale (HADS). The psychological measures were correlated with [18 F]PET‐FDG brain glucose metabolism. Multiple and linear regression and binary logistic regression were run to analyse data. The DT and HADS scores illustrated that 48% of patients were distressed, 19% were depressed and48% were anxious. Results showed that some subcortical areas activity, such as part of midbrain and of hypothalamus, was correlated with the DT scores. The Problem Checklist scores correlated with the activity of the same areas and included more regions in the limbic forebrain and brainstem. Compared with the DT and Problem Checklist, HADS‐Depression scores showed a more extensive pattern of correlation with brain activity, including limbic and cortical areas. The results highlighted that the DT scores correlated with the activity of brain areas typically involved in stress response. Indeed, hypothalamus metabolism was found to be the best predictor of distressed patients. Copyright © 2013 John Wiley & Sons, Ltd.